Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Make A Match Berbantuan Barang Bekas - Salsa Bhila; Sarintan N.Kaharu; Nuraini Nuraini; Azizah Azizah; Khairunnisa Khairunnisa (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study aims to improve students mathematatics learning outcomes by using the make a match learining model assisted by concrete media made from used goods in class 3 of SD Negeri Watusampu. The research method used in this study is classroom action research (CAR) which is carried out cyclically. The subjects in this study were 23 students of class 3 of SD Negeri Watusampu. The instruments used by researchers in collecting data were observation sheets, evaluation test questions, interviews and documentation. The data analysis techniques used in this study were quantitative data analysis and qualitative data analysis. The result of the study showed that using the make a match learning model assisted by concrete media made from used goods can improve the mathematics learning outcomes of class 3 students of SD Negeri Watusampu. The average value of classical learning completeness in cycle I was 52,17% then in cycle II there was an increase of 34,78% to 86,95%. The number of students who completed cycle I was 12 people, then in cycle II it increased to 20 students. The number of students who did not complete cycle I was 11 people, then in cycle II it decreased to 3 people. Based on the results and discussions that have been described above, it was obtained that by implementing the make a match learing model assisted by concrete media made from used goods, it can improve students’ mathematics learning outcomes in grade 3 of SD Negeri Watusampu. This is indicated by the classical learning completion achieved in cycle I of 52.17% rhen in cycle II it increased to 86,95%.